Desain Aplikasi Media Pembelajaran Untuk Membantu Pemahaman Siswa Tentang Konsep Geometri - Utin Desy Susiaty; Dwi Oktaviana (Universitas Indraprasta PGRI Jakarta, 2018)
The purpose of this research is to find out the design of an Adobe Flash CS5-based computer media on the quadrilateral concept material and how far this medium can facilitate understanding of the quadrilateral concept. It is a development research with stages consisting of needs analysis, computer media compilation, limited product trial and product evaluation. Data analysis performed for questionnaire of medium component evaluation is quantitative data analysis, while for questionnaire of medium material evaluation and student’s learning results, which are pre-test and post-test, is qualitative data analysis. The use of the medium can help students to improve their concept understanding of 42.969% and to keep answering with the right answer of 26.563%. The result of medium evaluation questionnaire on media being developed is good with average score of 33.75 from maximum score of 38. This shows that the media is useful to facilitate the quadrilateral concept learning in a classroom